2018
DOI: 10.18203/2320-6012.ijrms20180623
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of dexmedetomidine in two different doses to attenuate the hemodynamic changes during laparoscopic cholecystectomy

Abstract: Background: Laryngoscopy and laparoscopy lead to predictable hemodynamic changes. Dexmedetomidine is selective 2 agonist with dose dependent sedation, sympatholysis and analgesia, hence could provide stable hemodynamics during laparoscopic surgeries. The present study was aimed to compare the clinical efficacy of dexmedetomidine infusion in two different doses to attenuate the hemodynamic variations during laparoscopic cholecystectomy.Methods: Total 60 adult patients of ASA physical status I and II of both gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Dexmedetomidine decreases heart rate by augmenting the vagal nerve and blocking the cardio-accelerator nerves. This negative chronotropic effect is also attributed to reflex response for transient hypertension during initial part of infusion and subsequently it was due to diminished norepinephrine release and inhibition of central sympathetic outflow [7,8] . In our study after administration of the study drug, we observed the similar effect i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine decreases heart rate by augmenting the vagal nerve and blocking the cardio-accelerator nerves. This negative chronotropic effect is also attributed to reflex response for transient hypertension during initial part of infusion and subsequently it was due to diminished norepinephrine release and inhibition of central sympathetic outflow [7,8] . In our study after administration of the study drug, we observed the similar effect i.e.…”
Section: Discussionmentioning
confidence: 99%